Regeneration of the skin wound by two different crosslinkers: In vitro and in vivo studies - Naimeh Mahheidari; Morteza Alizadeh; Mohammad Kamalabadi farahani; Zohreh Arabpour; Nariman Rezaei kolarijani; Ali R. Djalilian; Majid Salehi (Iranian Journal of Basic Medical Sciences)
Objective(s): For designing a suitable hydrogel, two crosslinked Alginate/ Carboxymethyl cellulose (Alg/CMC) hydrogel, using calcium chloride (Ca2+) and glutaraldehyde (GA) as crosslinking agents were synthesized and compared.Materials and Methods: All samples were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), Blood compatibility (BC), Blood clotting index (BCI), weight loss (WL), water absorption (WA), pH, and Electrochemical Impedance Spectroscopy (EIS). Cell viability and cell migration were investigated using the MTT assay and the wound scratch test, respectively. Besides, the wound healing potential of prepared hydrogels was evaluated on the rat models with full-thickness skin excision. To further investigation, TGF β1, IGF-I, COL1, ACT-A (alfa-SMA), and GAPDH expression levels were also reported by RT-PCR. Results: Water absorption and weight loss properties were compared between different crosslinker agents, and the most nontoxic crosslinker concentration was determined. We have shown that GA (20 µl/ml) and Ca2+ (50 or 75 mM) enhanced the physical stability of Alg-CMC hydrogel, and they are nontoxic and suitable crosslinkers for wound dressing applications. Although in vivo assessments indicated that the GA (20 µl/ml) had a cytotoxic effect on tissue repair, Ca2+ (75 mM) boosted the wound healing process. Further, RT-PCR results revealed that TGF β1, IGF-I, COL1, ACT-A (alfa-SMA), and GAPDH expression levels were increased in GA (20 µl/ml). Moreover, this trend is the opposite in the Ca2+ (75 mM) treatment groups.Conclusion: This research shows that Ca2+ (75 mM) boosts tissue regeneration and wound healing process.